1996
DOI: 10.1177/0310057x9602400105
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Effects of Propofol following Bolus Administration in Sheep

Abstract: The effects of bolus administration of propofol (50 mg, 100 mg and 200 mg) on cerebral blood flow and cerebral metabolic rate for oxygen were examined in a chronically catheterized sheep preparation. Depth of anaesthesia was simultaneously measured using a withdrawal response to a noxious electrical stimulus and it was demonstrated that the 100 mg dose induced moderate sedation while the 200 mg dose induced relatively deep anaesthesia. Propofol caused transient dose-dependent decreases in cerebral blood flow, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…Studies in human and animal subjects have demonstrated that propofol induces dose‐dependent decreases in cerebral blood flow (CBF), cerebral metabolic rate for oxygen (CMRO 2 ) and intracranial pressure Neuronal activation in the brain is assumed to be coupled by parallel changes in regional metabolism and CBF . However, regarding regional changes, the total CMRO 2 is a fairly insensitive indicator of varying neuronal activity .…”
mentioning
confidence: 99%
“…Studies in human and animal subjects have demonstrated that propofol induces dose‐dependent decreases in cerebral blood flow (CBF), cerebral metabolic rate for oxygen (CMRO 2 ) and intracranial pressure Neuronal activation in the brain is assumed to be coupled by parallel changes in regional metabolism and CBF . However, regarding regional changes, the total CMRO 2 is a fairly insensitive indicator of varying neuronal activity .…”
mentioning
confidence: 99%
“…Die rasche Injektion von Propofol führt aber zu hohen Plasmaspitzenkonzentrationen [69]. Hohe Plasmapeaks von Propofol sind Ursache kurzzeitiger Abfälle des Herzminutenvolumens [117] bzw.…”
Section: Injektionsschmerzunclassified
“…Ludbrook et al [9] evaluated the effects of bolus doses of propofol on CBF and CMRO 2 in a chronically instrumented sheep model. CBF was measured by a Doppler transducer placed through a burr hole directly over the superior sagittal sinus using the venous outflow method.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Its effect on ICP is greater than that of hyperventilation and control of ICP with propofol restored SEPs in an animal model of intracranial hypertension [8]. Animal models have also demonstrated that propofol decreases both CBF and CMRO 2 [9,10,12]. The decrease in CBF and SCBF are greater in the forebrain than in the hindbrain or the spinal cord [12–14].…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation